Long pentraxin‐3 as an epithelial–stromal fibroblast growth factor‐targeting inhibitor in prostate cancer. (13th May 2013) - Ronca, Roberto; Alessi, Patrizia; Coltrini, Daniela; Di Salle, Emanuela; Giacomini, Arianna; Leali, Daria; Corsini, Michela; Belleri, Mirella; Tobia, Chiara; Garlanda, Cecilia; Bonomi, Elisa; Tardanico, Regina; et al.
Abstract Fibroblast growth factors (FGFs) exert autocrine/paracrine functions in prostate cancer by stimulating angiogenesis and tumour growth. Here dihydrotestosterone (DHT) up‐regulates FGF2 and FGF8b production in murine TRAMP‐C2 prostate cancer cells, activating a FGF‐dependent autocrine loop of stimulation. The soluble pattern recognition receptor long pentraxin‐3 (PTX3) acts as a natural FGF antagonist that binds FGF2 and FGF8b via its N‐terminal domain. We demonstrate that recombinant PTX3 protein and the PTX3‐derived pentapeptide Ac‐ARPCA‐NH2 abolish the mitogenic response of murine TRAMP‐C2 cells and human LNCaP prostate cancer cells to DHT and FGFs. Also, PTX3 hampers the angiogenic activity of DHT‐activated TRAMP‐C2 cells on the chick embryo chorioallantoic membrane (CAM). Accordingly, human PTX3 overexpression inhibits the mitogenic activity exerted by DHT or FGFs on hPTX3_TRAMP‐C2 cell transfectants and their angiogenic activity. Also, hPTX3_TRAMP‐C2 cells show a dramatic decrease of their angiogenic and tumourigenic potential when grafted in syngeneic or immunodeficient athymic male mice. A similar inhibitory effect is observed when TRAMP‐C2 cells overexpress only the FGF‐binding N‐terminal PTX3 domain. In keeping with the anti‐tumour activity of PTX3 in experimental prostate cancer, immunohistochemical analysis of prostate needle biopsies from primary prostate adenocarcinoma patients shows that parenchymal PTX3 expression, abundant in basal cells of normal glands, is lost in high‐grade prostatic intraepithelial neoplasia and in invasive tumour areas. These results identify PTX3 as a potent FGF antagonist endowed with anti‐angiogenic and anti‐neoplastic activity in prostate cancer. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.